Anticipatory pleasure in current psychosis: Cognitive and emotional correlates. (March 2021) - Rosebrock, Laina E; Waite, Felicity; Diamond, Rowan; Collett, Nicola; Bold, Emily; Chadwick, Eleanor; Teale, Ashley-Louise; Freeman, Daniel
Highlights: Anticipatory pleasure was associated with several important emotional factors. These factors included self-concept, paranoia-related avoidance, and insomnia. Associations with working memory were not significant. Abstract: Anticipation of pleasure – a key aspect of hedonic experience - is a motivating factor for engaging in activities. Low levels of anticipatory pleasure and activity are found in individuals with psychosis. Cognitive factors (e.g., working memory and IQ) have been a focus of explanation for anticipation of pleasure in psychosis. However, cognitive factors do not fully account for such difficulties. It is plausible that emotional factors (e.g., depression, self-beliefs) also contribute. We examined anticipatory pleasure in relation to cognitive and emotional processes in patients with current psychosis. 128 patients with persecutory delusions in the context of non-affective psychosis completed assessments of anticipatory pleasure, cognitive functioning, emotional processes, and activity. Lower anticipatory pleasure was significantly associated with depression, insomnia, negative-self beliefs, suicidal ideation, poorer psychological wellbeing, and paranoia-related avoidance. There were no significant associations with working memory, physical activity, or meaningful activity. Emotional factors may play a more significant role than cognitive difficulties in the experience of anhedonia in psychosis. However, the cross-sectional design precludes causal inferences. Future research should examine whether, for example, improving self-concept or reducing paranoia-related avoidance leads to improvement in anticipatory pleasure in patients with psychosis.